Retrofitting CNC milling machine (pilot study ) / Ir. Abdul Rahman Omar and V. Azad Chacko - Omar, Abdul Rahman; Chacko, V. Azad; Pusat CADEM, . (1994)
The successes of machining operation in machine tool depend on the experience and skill of the machine operator. A significant amount of work has been done on the machine to be controlled by computer. The on-line control serves as the key to this problem. This pilot study also emphases the important of interface design between machine operator, computer and the machine tool. The designed controller will ease the integration work of the three elements mentioned above. Another significant study carried out is the software element. The software has the features to understand the G-code and the M-code of the Computerised Numerical Controlled machine.